Implementasi Model Pembelajaran Inkuiri dalam Menulis Kritis melalui Teknologi Literasi Digital - Albaburrahim Albaburrahim; Suyono Suyono; Didin Widyartono (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the implementation of the inquiry learning model in critical writing through digital literacy technology. This research is also to determine the implementation of inquiry learning in critical writing by utilizing digital literacy technology. This research method uses research and development methods used in this research. Based on development standards for learning system design, this investigation was carried out procedurally. The procedure includes preparation, implementation and evaluation stages. The data collection in this research was through classroom observations, student and teacher interviews, as well as analysis of student written work produced through digital literacy technology. Data analysis in this research involved collecting, processing and interpreting data from students' literacy activities and written production. Data can be presented in the form of interactions on digital literacy platforms, student responses, or the quality of written results. The results of this research show that the inquiry learning model can be useful in making it easier for students to write critically, supported by the existence of digital literacy technology which has developed rapidly. Digital literacy technologies enable quick and easy access to a wide range of information sources in critical writing contexts.